Desafios e soluções de controle e estabilização de robôs bípedes - Catulé, Antônio Pedro de Freitas Barbosa (2021)
The use of robots in the human being's daily life has been more and more frequent, whether in the performance of household chores or in the execution of tasks that involve risks. Thus, there is a constant need to search for new possibilities and technologies that provide the realization of such activities. Among the countless fields of research, biped robots are one of the most studied, with the problem of stability being one of the most common. The work aims to carry out a literature review regarding the constructive and control aspects of bipedal robots, in addition to the analysis of the advantages and disadvantages of elements that characterize the development and operationalization of movements, in order to propose improvements in the robot being developed by Department of Mechanical Engineering at UFSCar. Thus, it is concluded that despite being a wide field of study and in constant evolution, it brings as propositions the addition of more degrees of freedom, force sensors and tail removal for the implementation of the biped robot, thus enabling constructive methods and more efficient mobility than those currently used.